Development of prosthetic terminal device with sensory feedback / Nur Afiqah Hashim - Nur Afiqah , Hashim (2017)
There are numbers of prosthetic terminal devices which offer functional restoration to individual with upper limb deficiencies. Nowadays, there are great advancement in the electrical prosthesis. The most physically neutral electrical upper limb amputee prosthesis is myoelectric prosthesis system that use muscle activity from the remaining limb for the control of terminal device or joint movement. Myoelectric prosthesis present in one-way communication which is from the user to the prosthesis. One of the challenges facing prosthetic designers and engineers is to restore the missing sensory function inherit to hand amputation. The user are able to send the signal from the remaining muscle to the prosthesis but the prosthesis are not able to send the signal back to the user. Therefore, without noticing, the user may exert extra force and can accidently squeeze the object they hold. The objective of this research is to establish two-way communication prosthetic system by developing a prosthetic terminal device with sensory feedback. The terminal device will monitor amount of force exerted on an object and amount of force is translated into vibration that are identifiable by the skin of the user. This prosthesis allows user to control and supply adequate amount of force while grasping object. For the first part, a myoelectric controlled prosthesis, named ‘smartGrip’ that comes with a skin electrode, FSR sensor, vibration motor, microcontroller, battery and electrical terminal device was fabricated. The terminal device reprogrammed with a new setup and control unit. On the second part, analysis on two mechanical and one electrical terminal device was executed as a part of the study to investigate standard characteristic of terminal device. The performances of the device were tested on one transradial amputee and two normal subject. QUEST survey was also executed to evaluate user’s satisfaction toward the hand. The average force exerted by the mechanical terminal device is slightly lower than the electrical terminal device. Force distributed uniformly at different opening angle by electrical terminal device but changing with increase in opening angle by mechanical